Lung Injury on Antiretroviral Therapy in Adults With Human Immunodeficiency Virus/Tuberculosis. (26th June 2019) - Ravimohan, Shruthi; Auld, Sara C; Maenetje, Pholo; Ratsela, Nelly; Mlotshwa, Mandla; Ncube, Itai; Smith, Jonathan P; Vangu, Mboyo-Di-Tamba; Sebe, Modulakgotla; Kossenkov, Andrew; Weissman, Drew; Wallis, Robert S; et al.
Abstract: Background: Immune restoration on antiretroviral therapy (ART) can drive inflammation in people living with human immunodeficiency virus (HIV) who have pulmonary tuberculosis (TB), but its effects on the lungs have not been assessed. We evaluated associations between pulmonary inflammation, recovery of pathogen-specific CD4 T-cell function, and lung injury prior to and after ART initiation in adults with HIV and pulmonary TB. Methods: This was a prospective cohort study in South Africa, following adults with HIV and pulmonary TB prior to and up to 48 weeks after ART initiation. Pulmonary-specific inflammation was defined as total glycolytic activity (TGA) on [18]F-fluorodeoxyglucose (FDG) positron emission tomography–computed tomography (PET-CT) at baseline and 4 weeks after ART initiation. Spirometry, respiratory symptom tests, and flow cytometry were performed at the same times to assess lung involvement and the frequency of mycobacteria-specific CD4 T-cells. In addition, we evaluated lung function longitudinally up to 48 weeks after ART initiation. Results: Greater lung TGA on FDG PET-CT was associated with worse lung function and respiratory symptoms prior to ART initiation, and nearly half of subjects experienced worsening lung inflammation and lung function at Week 4 of ART. Worsening Week 4 lung inflammation and pulmonary function were both associated with greater increases in pathogen-specific functional CD4 T-cell responses on ART, and early decreases in lung function were independently associated with persistently lower lung function months after TB treatment completion. Conclusions: Increases in pulmonary inflammation and decreases in lung function are common on ART, relate to greater ART-mediated CD4 T-cell restoration, and are associated with the persistent impairment of lung function in individuals with HIV/TB. Abstract : In this study from South Africa, approximately half of all adults with human immunodeficiency virus and pulmonary tuberculosis had increases in lung inflammation and decreases in lung functioning as their CD4 T-cell function recovered on antiretroviral therapy.